(untitled) (Journal of Pathology of Nepal, 2015)
The hospital acquired infections are becoming common in our hospitals lately. These infections are difficult to treat and maybe life threatening. Hospital acquired infection can be minimized or eradicated by good Infection Prevention and Control guidelines and good hand hygiene practices. The success of Infection Prevention and Control guidelines program in any hospital is largely impacted by the organizational culture. In any health care setting the management is challenged by the organizational culture to change of any kind. Where implementation of Infection Prevention and Control guidelines program is easily implemented in some hospitals it is very difficult in others. Moreover, hand hygiene is not only biomedical practice but also has more behavioral factors.